Effect of Maxillary Sinus Membrane Perforation on Vital Bone Formation and Implant Survival: A Retrospective Study. Issue 8 (1st August 2013) - Froum, Stuart J.; Khouly, Ismael; Favero, Giovanni; Cho, Sang‐Choon
Abstract : Background: The maxillary sinus augmentation procedure (SAP) using the lateral window technique has been documented to be a highly predictable procedure. However, the most common intraoperative complication has been reported to be maxillary sinus membrane perforation (MSMP). The present study evaluates the percentage of vital bone and implant survival in sinuses that had perforations repaired during surgery versus a non‐perforated sinus group. Methods: Data were obtained retrospectively from an Institutional Review Board–approved anonymous database at New York University, Kriser Dental Center, Department of Periodontology and Implant Dentistry, New York, New York, from 23 patients who had undergone SAP with a total of 40 treated sinuses. Sinuses were grafted with mineralized cancellous bone allograft, anorganic bovine bone matrix, or biphasic calcium phospate. Perforation complications occurred in 15 sinuses with 25 non‐perforated sinuses. All perforations were repaired during surgery with absorbable collagen membrane barriers. Histologic cores were taken from all treated sinuses 26 to 32 weeks after surgery. The implant success rate of 79 placed implants was recorded. Results: The average percentage of vital bone was 26.3% ± 6.3% in the perforated (repaired) sinuses versus 19.1% ± 6.3% in the non‐perforated sinuses. The differences were statistically significant (SS). The implant success rate was 100% (35 of 35) compared to 95.5% (43 of 45) in the perforated/repaired vs. non‐perforated sinuses, respectively. There was no SS difference in implant failure rates. Conclusions: The augmented sinuses in this study that exhibited MSMPs that occurred during the SAP (which were treated during surgery) show SS greater vital bone percentages compared with the non‐perforated sinus group. There were no SS differences in implant survival in the perforated versus non‐perforated groups. In this study, sinus MSMPs, when properly repaired during surgery, do not appear to be an adverse complication in terms of vital bone production or implant survival.